Pengembangan Bahan Ajar IPADigital Bermuatan Etno-STEM Proses Pembuatan Jajanan Tradisional Sidoarjo Materi Gaya dan Gerak Benda untuk Melatih Literasi Sains pada Siswa Sekolah Dasar - Juniawan, Eko Rahmad; Sumarni, Woro; Prasetya, Agung Tri (Postgraduate, University of Mataram, 2024)
This study aims to develop digital science teaching materials with Ethno-STEM content to train elementary students' scientific literacy. The research method used is the ADDIE Research and Development (R&D) model (Analyze, Design, Development, Implementation and Evaluation). The results of the feasibility of digital science teaching materials obtained a percentage of 92.42% with very feasible criteria. The effectiveness of digital science teaching materials was declared effective by the results of the paired t-test which showed that there was an average difference in the pretest and posttest data, and the n-gain results scored 0.40 with the criteria of being effective. The results of the student response questionnaire after the learning process obtained a percentage of 90.35%; as well as the results of the teacher's response questionnaire after the learning process obtained a percentage of 90.62%. The results of student and teacher responses obtained very positive criteria. The conclusions of this study are that digital science teaching materials with Ethno-STEM content are effective in training scientific literacy for grade IV elementary school students.